PERAMALAN HARGA MINYAK MENTAH STANDARWEST TEXAS INTERMEDIATEDENGAN PENDEKATAN METODEARIMA - Syahril Faozi; Wellie Sulistijanti (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Crude Oil is an important commodity. Because crude oil is a much needed source of energy all over the world. So that changes of oil prices will greatlyaffect the state of a country's economy. The price of crude oil in certainconditions has a significant increase and decrease. Rising crude oil prices willhave an impact on both exporting and importing countries in terms of inflation,stock prices and interest rates. Thus, statistical techniques that can be used toforecast time series data types are ARIMA (Autoregressive Integrated MovingAverage). Based on the above description of the objectives to be achieved is toforecast the price of crude oil on June 23 - July 3, 2016. From the forecastingresults with Box-Jenkins method, the best ARIMA model obtained is ARIMA (1,1,1) with forecasting model:   Keywords: ARIMA, Oil Price, Forecast